State anger and creative process engagement in organisational context - Costa, C.; Zhou, Q.; Ferreira, A. (Proceedings of the 30th EGOS Colloquium, 2014)
This paper presents a study on the impact of State Anger (SA) on Creative Process Engagement (CPE) on a daily basis in an organizational context. Applying a within-person perspective it examines the daily effect of SA on the CPE. It contemplates the role of moderators, such as: such as Emotion Regulation (ER) - Reappraisal (RE) and Suppression (SU); Work Engagement (WE); and High Effort Tasks (HET) in the relationship between SA and CPE. The sample in the study is of workers from two companies. Participants completed a general questionnaire and then a daily questionnaire for one working week.